Two dimension numerical modeling of wave and wind induced currents and bed morphology evolution at Phan Ri - Binh Thuan coastal zone - Hoan, Le Xuan; Nam, Pham Thanh (Vietnam Journal of Mechanics, 2005)
Based on the 2DH model for calculating the wave induced currents, established by Christopher G. Koutitas [1], a 2DH numerical model for calculating the wave and wind induced currents (current-model) is developed with taking additional account of shear stress due to wind and eddy viscosity components. A 2DH numerical model for calculating the sediment transport and bed morphology evolution (sand-model) is developed and linked to the above current- model. The wave parameters used for the input of the models are obtained from the RCPWAVE model. This paper presents some numerical results of calculating the currents induced by wind and waves and bed morphology evolution at Phan Ri – Binh Thuan coastal zone for two typical cases of wind: NE and SW monsoons.